Changes in upper limb joint power during round-off in female gymnastics - Brtva, P.; Irwin, G.; Farana, R. (ISBS Proceedings Archive (Michigan), 2022)
The aim of the current study was to investigate joint power changes in upper limb joints during the support phase of three round-off (RO) techniques (reverse, parallel, T-shape). Twenty young female gymnasts performed 18 RO trials in three different techniques. Kinematic and kinetic data were collected for each trial. Statistical parametric mapping of mean joint power was performed to compare differences between techniques. Results demonstrated that the reverse technique had lower joint powers during the absorption and propulsion phases of the skill compared to the other techniques. The T-shape technique elicited greater wrist absorption, and elbow power generation. Wrist and elbow joint power absorption-propulsion peaks follow a distal-proximal pattern which reversed to a proximal-distal sequence of movement coordination across all techniques.